Perancangan Sistem Data Hasil Belajar Murid SMA Islam Said Na’um Berbasis Java - Purwanti Purwanti (Jurnal Informatika Universitas Pamulang, 2020)
SMAI Said Na'um is a senior secondary education institution in the Jakarta area. The system at this school has not used a computerized system optimally so it has several problems. The problems in Said Na'um SMAI include recording values using paper files which take a very long time. Lack of storage media, the data search process takes a little time. The information received is currently less fast and less accurate. Often there are data errors or inaccurate data in making reports. Data storage that is still in the form of physical files can cause damage to data. Based on this information, the research carried out aims to create an information system for learning assessment for students of Said Na'um Senior High School, Central Jakarta. This research was conducted by creating a data system on student learning outcomes at Said Na'um Islamic Senior High School using a Java-based programming language.